Communicating health strategies for health promotion - Corcoran, Nova (Los Angeles, California Sage, 2013)
This textbook explores current research and practice in the field and examines the knowledge and skills needed by health practitioners to promote and improve the health of the population.
Theories and Models -- Social and Psychological Factors -- Reaching Unreachable Groups and Crossing Cultural Barriers -- Mass Media -- Information Technology -- Using Settings -- Evidence-Based Practice -- Using Evaluation -- Bridging Theory and Practice -- ten different health promotion campaigns.
Includes bibliographical references (pages 200-223) and index.
Keywords: Health promotion; Health education